Analisis Hubungan antara Iman kepada Tuhan Yesus Kristus, Putera Allah dan Penghayatan Hidup Doa Para Frater CSE Komunitas Studi Landak, Kalimantan – Barat - Angelo Luciani Moa Dosi Woda (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2021)
In the formation of priestly candidates, there are 2 (two) important inseparable dimensions, namely, intellectual formation and spiritual direction. In the reality, how can we justify the empirical relationship between the faith of Jesus Christ with the life of prayer of the holy ordination candidate? What is the real contribution to the advancement of the priestly candidates' formation at the high seminary? To solve that problem, we take a quantitative descriptive research with the approach of descriptive analysis. In this way, we investigate the relationship between the variable of the faith of Jesus Christ, Son of God with the life of prayer of CSE Brothers. We have confidence that the relationship between the faith of Jesus Christ and the life of prayer will bring the priestly candidates for the living encounter with God in Christ and it will change their life entirely. For that reason, we formulate a minor hypothesis as follows. The Encounter with the Lord Jesus Christ, Son of God as a Spiritual Foundation for the CSE Brothers at Scholastic Community in Landak, West - Borneo. The result of the research explains that the minor hypotheses can be accepted. We record that there is a significant relationship between the faith of Jesus Christ, Son of God with the life of prayer of CSE Brothers at Scholastic Community in Landak, West - Borneo. There is a positive relationship between the faith of Jesus Christ, Son of God with the life of prayer of CSE Brothers at Scholastic Community in Landak with the percentage scale between 63% and 55%.